The Role of Madrasah Principal as a Motivator in Improving Teacher Performance - Harahap, Abdul Hamid Haji; Nonci, Riswan D; Na'imah, Na'imah (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2023)
This research on motivation (self-transcendence) of MA Hamalatul Qur'an Yogyakarta teachers aims to determine the role of institutions or principal as motivators to optimize teacher performance at MA Hamalatul Qur'an Yogyakarta. This research employed a descriptive qualitative approach. The subjects of this study included the teachers who teach at the MA Hamalatul Qur'an Yogyakartal. The data collection techniques used were interviews and observations. The theory used is Maslow's Hierarchy of Needs theory where there are several levels of needs needed to increase work motivation. In this study, this theory was used to determine the achievement of the spiritual needs of teachers who teach at MA Hamalatul Qur'an Yogyakarta School. Also, this research studied whether all the needs contained in Maslow's theory can be met by institutions to increase the motivation of teachers. The results showed that the role of school principal in increasing motivation, facilities, and appreciation of teachers' performance is needed. However, there are shortcomings or limitations in terms of the allocation of funds and others that make several things at the level of these needs could not be met. Despite these shortcomings, the enthusiasm of teachers to continue teaching and sincerity in conveying knowledge is an important thing that embodies self-transcendence